Pengembangan Web Portal Landing Page E-Commerce Dengan Pola Single Page Application - Alif Sani Ekasmara; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Based on studies conducted by Google and Temasek in 2018, Indonesia has great digital economic potential. This will be very good if business people in Indonesia can exploit this potential. But businesses in Indonesia which are dominated by small and medium scale entrepreneurs (MSMEs) will have some problems if they have to develop their own business websites. To overcome the following problem, an e-commerce landing page portal website was developed. With so much data being processed and transferred between servers and clients, the system will be developed using a single-page application pattern. The system will be developed with a prototyping model in the development process. The system interface was developed with the ReactJS library and on the server using NodeJS and Express framework. Communication between server and client is done with JSON. The results of the study found that there were 3 actors, 41 functional needs, and 3 non-functional needs. System testing is done by white-box and black-box testing. The results of testing each need found 100% valid.